Blockchain Technology for Tracking Chain Supply - Riko Herwanto; Yan Aditiya Pratama; Handoyo Widi Nugroho; Wasilah Wasilah; Hary Sabita (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The adequate technology was the architecture that was distributed through the block chain technology which had authorizations for securing data storage and for accessing any piece of information anytime and anywhere. The objective of this study was to find out whether the issues of the supply chains and the block chain were able to be solved. The hypothesis of this study was suitable for the supply chain management in the block chain architectures. In this study, a survey was conducted to validate the issues of supply chain management and to obtain the requirement for a supply chain software system.Keywords: Supply Chain, Supply Chain Management, Blockchain, Distributed Architecture, Security, Traceability, Information Integration, Interoperability